Research of toxicity of chitosan-based film-forming compositions - Dubinina, Antonina; Letuta, Tatiana; Frolova, Tatiana; Savinova, Helena; Bolshakova, Galina; Novikova, Vira (Technology audit and production reserves, 2017)
The object of research is chitosan-based film-forming compositions with the addition of decoctions from medicinal plants: Sweet flag, Senegalia catechu, Ledum, Bergenia crassifolia; Common yarrow, Eucalyptus globulus, Eleutherococcus senticosus, Hypericum perforatum; Chamaenerion angustifolium, Iceland moss, Calendula officinalis, Urtica; Peppermint, Potentilla alba, Common tansy, Plantago major; Artemisia absinthium, Motherwort, Sage, Common sunflower. Medicinal herbs have biological activity (toxicity), which accompanies the main therapeutic effect and depends on the dose. Toxicity is not observed in all medicinal herbs, but among them there are strong and even poisonous. Presented in the composition, medicinal herbs based on 2 % chitosan are not studied for toxicity, therefore, to establish the safety of their use as a packaging for fruit and vegetables, this must be done. The developed compositions are examined for: 1) toxicity using bacteriological methods by sowing on 5 % blood agar; 2) manifestation of hemolysis zones and growth of B.cereus culture by diffusion into agar (well method). During the research, positive results are obtained: 1) all samples are not toxic; 2) hemolysis zones are not identified; 3) there is a suppression of the growth of B.cereus culture, which grew on the surface of blood agar (growth retardation zones of culture B.cereus 0–34 mm). Further expansion of the study will allow the use of chitosan-based film-forming compositions that have differentiated properties with respect to solubility, sorption, bactericidal and antioxidant effects as a factor in increasing the biological value of food in the absence of toxicity in fruit and vegetable products.